Proposed conceptual model for E-service quality in Malaysian universities - Al-Nuaimi, I.T.I. (Institute of Electrical and Electronics Engineers Inc., 2014)
There is a significant role of e-services quality in achieving success or failure of online organizations. It can increase their competitive advantages in the target markets, and enhance the relationships with customers and their satisfactions. There is no agreement about what service quality is and how it should be measure. Accurate measurement of the quality of electronic service is a complex process due to the nature of the service because it is immaterial and untypical product. It has been indicated through the literature that there is a lack of universal set of definitions, model and dimensions for service quality measurement. Since the service quality measures in higher education have great importance in achieving high tuition-based returns, e-service institutions of higher education are subjected to continuous pressure to surpass their competitors in presenting better e-service quality. This paper proposes an e-service quality conceptual model for measuring e-service quality in higher education sectors in Malaysia. Nine dimensions are proposed for this model based on reviewing the related literature. The dimensions include efficiency, availability, privacy/security, fulfilment, reliability, web design, interactivity, information, and responsiveness. Results of this paper may help to build a proper scale to measure the quality of e-services in higher education, which assist to improve the performance and effectiveness of e-services to achieve users' satisfaction. Â© 2014 IEEE.